DNA damage and protein oxidation associated with ageing correlate with cognitive dysfunction in a Malaysian population - Sani, NFA; Damanhuri, MHA; Hamzah, AIZA; Abu Bakar, ZH; Tan, JK; Aripin, KNN; Rani, MDM; Noh, NA; Shamaan, NA; Razali, R; Yusof, YAM; Mazlan, M; et al. (Taylor & Francis Ltd, 2024)
Indexed by WOS/Scopus/ERA